Excess synaptojanin 1 contributes to place cell dysfunction and memory deficits in the aging hippocampus in three types of Alzheimer's disease - Miranda, André Miguel Lopes (2018)
The phosphoinositide phosphatase synaptojanin 1 (SYNJ1) is a key regulator of synaptic function. We first tested whether SYNJ1 contributes to phenotypic variations in familial Alzheimer's disease (FAD) and show that SYNJ1 polymorphisms are associated with age of onset in both early- and late-onset human FAD cohorts. We then interrogated whether SYNJ1 levels could directly affect memory. We show that increased SYNJ1 levels in autopsy brains from adults with Down syndrome (DS/AD) are inversely correlated with synaptophysin levels, a direct readout of synaptic integrity. We further report age-dependent cognitive decline in a mouse model overexpressing murine Synj1 to the levels observed in human sporadic AD, triggered through hippocampal hyperexcitability and defects in the spatial reproducibility of place fields. Taken together, our findings suggest that SYNJ1 contributes to memory deficits in the aging hippocampus in all forms of AD.